DIFFERENTIAL MANIFESTATIONS OF INLAMMATORY BOWEL DISEASE (IBD) BASED ON RAGE AND IMMIGRATION STATUS. (21st January 2021) - Crowe, Brooks; Khalessi, Ali; Xia, Yuhe; Rubinfeld, Gregory; Baylor, Jessica; Radin, Arielle; Liang, Peter; Chen, Lea Ann
Abstract: Background: The increasing incidence of IBD globally presents an important opportunity to study intrinsic and environmental determinants of disease development. We examined how race and immigration status influence IBD manifestations, treatments, and outcomes in a diverse, tertiary-care public hospital that serves predominantly the uninsured and underinsured. Methods: We conducted a single-center retrospective review of all IBD patients treated from 1997–2017. Using logistic regression modeling, we compared disease onset, treatment, and outcomes by race (White, Black, Hispanic, Asian) and immigration status (US-born vs. foreign-born). To assess for the potential confounder of race in analyses of US versus foreign-born subjects, we further evaluated differences in IBD characteristics among foreign-born patients in each of the four racial groups. Results: A total of 577 patients were identified, of which 29.8% were White, 27.4% Hispanic, 21.7% Black, and 13.0% Asian. Of these patients, 260 had a confirmed country of birth, with 69.6% being foreign-born. The time between IBD diagnosis and last documented follow up was not statistically different between races, nor by foreign versus US-born status. Asian IBD patients were less likely than White IBD patients to be female (OR 0.38, 95% CI: 0.20, 0.69). Among ulcerative colitis (UC) patients, Asians were more likely than White patients to have isolated proctitis (OR 10.34, 95% CI: 1.58, 203.08). Black patients were less likely to be diagnosed with UC (OR 0.57, 95% CI: 0.36, 0.91) and more likely to undergo IBD-related intestinal resection (OR 2.49, 95% CI: 1.40, 4.50), though the opposite was true in foreign-born Black patients. Overall, foreign-born patients were more likely to be diagnosed with UC (OR 1.77, 95% CI: 1.04, 3.02). They were also less likely to be diagnosed before 16 years of age (OR 0.19, 95% CI: 0.08, 0.41), have undergone intestinal resections (OR 0.39, 95% CI: 0.19, 0.83), or have received biologics (OR 0.43, 95% CI: 0.25, 0.76). No single race accounted for the decreased use of biologics or intestinal resections among foreign-born patients. Conclusions: IBD phenotype varies by race, although foreign-born patients of all races show evidence of later onset and milder disease. As our study was performed in a large single-center safety-net hospital, our study design minimized socioeconomic confounders. These findings may aid in disease prognostication and clinical management and furthermore may provide insight into intrinsic and environmental influences on IBD pathogenesis.